Assessment of Level of Stress in Undergraduate Medical Students of a Private Medical College in Pakistan - Izza Umbrin, Sana Shah, Sana Siddiqui, Saadia Rehman, Washma Asad, Unaiza Ambreen (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Extensive and demanding medical curriculum manifests itself as stress in medical students. Different individuals perceive stress differently. Stress greatly affects academic performance and mental health of medical students. Levels of stress vary with gender, year of study and living conditions of students. Objective: This study was performed to evaluate stress levels of undergraduate medical students in Pakistan. Study Design: Descriptive cross-sectional study. Duration: Two months from December 2021 to January 2022. Setting: Multan Medical and Dental College, Multan, Pakistan. Methods: First year, second year, third year, fourth year and final year MBBS students from Multan Medical and Dental College (MMDC), Pakistan were selected through census sampling. Students were asked to fill Perceived Stress Scale Questionnaire (PSSQ-10). After quantitative data was analyzed through descriptive studies, all students were divided into three groups: low stress, moderate stress, and high stress bearers. Results: Among 427 students, 54 (12.65%) students had low stress, 311 (72.83%) students had moderate stress and 62 (14.52%) students had high stress. Females were more stressed compared to males. Among high stress group, 18% females were affected compared to 9% males. 73.94% females had moderate stress compared to their male counterparts i.e., 71.08%. Male boarders were less stressed compared to female boarders. Students of first year had lowest perceived stress (M=9, SD=3.82), whereas final year students had highest stress (M=30.5, SD= 2.8), followed by third year, fourth year, second year and first year students. Practical implication: This study is intended to give an insight into level of stress that medical students are encountering. Early intervention by concerned authorities for high levels of stress can enable students to handle stress in a better way in years to come and prevent them from developing any psychiatric disorders. Students with mild and moderate stress levels can be helped to prevent more serious stress conditions. A less stressful environment is congenial for students for academics and mental health. Conclusion: The study highlights the issue of prevalence of perceived stress among medical students, which is affecting their academic performance and health. Keywords: Moderate Stress, Under-Graduate Perceived Stress Scale , Discomfort, Academic,